A Typology of Interactional Patterns Between Youth and Their Stepfathers: Associations with Family Relationship Quality and Youth Well‐Being. Issue 2 (9th March 2018) - Jensen, Todd M.
Abstract : Stepfamilies are an increasingly common family form, many of which are headed by a resident mother and stepfather. Stepfather–child relationships exert notable influence on stepfamily stability and individual well‐being. Although various stepfather roles have been observed, more research is warranted by which stepfather–child interactions are explored holistically and across a variety of life domains (e.g., recreational, personal, academic, and disciplinary). Thus, the primary purpose of the current study is to explore varying interactional patterns between youth and their stepfathers. A latent class analysis is conducted using a representative sample of 1, 183 youth (53% female; mean age = 15.64 years, SD  = 1.70 years; 62% non‐Hispanic White) residing in mother–stepfather families from Wave I of the National Longitudinal Study of Adolescent to Adult Health. Latent‐class enumeration processes support a four‐class solution, with latent classes representing inactive, academically oriented, casually connected, and versatile and involved patterns of youth–stepparent interaction. Notable differences and similarities are evident across patterns with respect to family relationship quality, youth well‐being, and socio‐demographic characteristics. Differences are most stark between the inactive and versatile and involved patterns. Ultimately, the results showcase notable variation in youth–stepparent interactional patterns, and one size does not necessarily fit all stepfamilies. Family practitioners should be mindful of variation in youth–stepparent interactional patterns and assist stepfamilies in seeking out stepparent–child dynamics that are most compatible with the needs and dynamics of the larger family system. Abstract : Las familias ensambladas son cada vez más una forma común de familia, muchas de las cuales están encabezadas por una madre y un padrastro residentes. Las relaciones entre el padrastro y los niños ejercen una influencia notable en la estabilidad de la familia ensamblada y en el bienestar individual. Aunque se han observado distintos roles de los padrastros, se necesitan más investigaciones en las que las interacciones entre el padrastro y los niños se analicen íntegramente y en diferentes ámbitos de la vida (p. ej.: recreativo, personal, académico y disciplinario). Por lo tanto, el objetivo principal del presente estudio es analizar patrones interactivos variados entre los jóvenes y sus padrastros. Se realiza un análisis de clases latentes utilizando una muestra representativa de 1183 jóvenes (el 53 % de sexo femenino; edad promedio = 15.64 años, DT = 1.70 años; el 62 % blancos no hispanos) que viven en familias compuestas por una madre y un padrastro de la serie I del "Estudio Longitudinal Nacional de la Salud Adolescente a Adulta" (National Longitudinal Study of Adolescent to Adult Health). Los procesos de enumeración de las clases latentes respaldan una solución de cuatro clases, donde las clases latentes representan patrones de interacción inactivos, orientados a lo académico, conectados ocasionalmente y versátiles e interesados entre los jóvenes y los padrastros. Se observan diferencias y similitudes notables entre los patrones con respecto a la calidad de la relación familiar, al bienestar de los jóvenes y a las características sociodemográficas. Las diferencias son más marcadas entre los patrones inactivos y versátiles e interesados. Finalmente, los resultados exhiben una variación notable en los patrones interactivos entre los jóvenes y los padrastros, por lo tanto, no necesariamente existe un criterio único aplicable a todas las familias esambladas. Los médicos familiares deben estar al tanto de la variación en los patrones interactivos entre los jóvenes y los padrastros y ayudar a las familias ensambladas a buscar una dinámica entre los jóvenes y los padrastros que sea más compatible con las necesidades y la dinámica del sistema familiar más amplio. Abstract : 继亲家庭日益成为一种普遍家庭模式。很多继亲家庭中的家长是继父和居家母亲。继父‐儿童关系对于继亲家庭稳定性和个人健康有显著影响。虽然继父扮演各种角色, 我们需要更多研究来整体探讨继父‐儿童在生活不同方面的互动(例如娱乐, 个人, 学术, 以及纪律)。该研究的主要目的是探讨青少年和其继父之间不同的互动模型。我们使用一个由1183位居住在由母亲和继父构成的家庭中青少年(53%女孩;平均年龄=15.64, SD=1.70年;62%为非墨西哥裔白人)构成的样本从青少年到成人家庭国家纵向研究第一阶段进行了一项潜在等级分析。潜在等级列举过程支持一项四个等级解决方案, 其中潜在等级代表不活跃, 学术型, 随意联系的, 多样性以及积极参与青少年‐继父互动模式。显著区别和相似性家庭关系质量, 青少年健康, 以及社会人口特点方面不同模式间很明显。不活跃模式和多样化以及参与模式之间区别最明显。最后, 结果显示青少年‐继亲互动模式显著变异。一种模式并不适用于所以继亲家庭。家庭心理咨询师应该关注青少年‐继亲互动模式中的变异, 并帮助继亲家庭寻找出最适合其需求以及大家庭 系统关系的继亲‐儿童互动模式。